2021
DOI: 10.1158/0008-5472.can-20-3944
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of ACADM-Mediated Fatty Acid Oxidation Promotes Hepatocellular Carcinoma via Aberrant CAV1/SREBP1 Signaling

Abstract: Lipid accumulation exacerbates tumor development, as it fuels the proliferative growth of cancer cells. The role of medium-chain acyl-CoA dehydrogenase (ACADM), an enzyme that catalyzes the first step of mitochondrial fatty acid oxidation, in tumor biology remains elusive. Therefore, investigating its mode of dysregulation can shed light on metabolic dependencies in cancer development. In hepatocellular carcinoma (HCC), ACADM was significantly underexpressed, correlating with several aggressive clinicopatholog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“… 242 Furthermore, downregulation of acylcarnitine translocase (SLC25A20) in the mitochondrial matrix is observed in both HCC and CCA (TCGA, www.firebrowse.org ) and was shown to suppress FAO and promote HCC proliferation as well as metastasis. 243 Furthermore, enzymes in the FAO process, such as medium-chain acyl-CoA dehydrogenase 244 and long-chain acyl-CoA dehydrogenase, 245 have potential tumour suppressor roles in HCC. 244 , 245 Therefore, FA utilisation for structural and messenger molecules, rather than storage or energy sources, supports HCC development and progression.…”
Section: Deregulation Of Lipid Metabolism In Liver Cancermentioning
confidence: 99%
See 1 more Smart Citation
“… 242 Furthermore, downregulation of acylcarnitine translocase (SLC25A20) in the mitochondrial matrix is observed in both HCC and CCA (TCGA, www.firebrowse.org ) and was shown to suppress FAO and promote HCC proliferation as well as metastasis. 243 Furthermore, enzymes in the FAO process, such as medium-chain acyl-CoA dehydrogenase 244 and long-chain acyl-CoA dehydrogenase, 245 have potential tumour suppressor roles in HCC. 244 , 245 Therefore, FA utilisation for structural and messenger molecules, rather than storage or energy sources, supports HCC development and progression.…”
Section: Deregulation Of Lipid Metabolism In Liver Cancermentioning
confidence: 99%
“… 243 Furthermore, enzymes in the FAO process, such as medium-chain acyl-CoA dehydrogenase 244 and long-chain acyl-CoA dehydrogenase, 245 have potential tumour suppressor roles in HCC. 244 , 245 Therefore, FA utilisation for structural and messenger molecules, rather than storage or energy sources, supports HCC development and progression.…”
Section: Deregulation Of Lipid Metabolism In Liver Cancermentioning
confidence: 99%
“…It had been reported that ACADM is associated with the progression of some tumors, especially those closely related to lipid metabolism, such as neuroblastoma and breast cancer (Ma et al, 2021;Hsieh et al, 2019;Yu et al, 2019). Interestingly, we found that ACADM plays an anticancer role in most tumors such as hepatocellular carcinoma and neuroblastoma (Hsieh et al, 2019;Ma et al, 2021). However, it has been reported that ACADM enhances the invasion and metastasis ability of breast cancer cells (Yu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Medium-chain acyl coenzyme dehydrogenase (ACADM) is a functional component that promotes β-oxidation, and SREBP-1 is a negative transcriptional regulator of ACADM. Cav1 is an important factor involved in tumorigenesis and progression of many cancers, and Cav1 can regulate fatty acid metabolism by activating SREBP-1, thereby inhibiting ACADM in HCC [ 85 ].…”
Section: Regulation Of Lipid Metabolism In the Tumor Microenvironmentmentioning
confidence: 99%